Seeking alternative financing sources for African SMEs/micro-enterprises: the case of crowdfunding - (:unkn) unknown (My University, 2025)
Crowdfunding (CF) is an innovative solidarity financing, halfway between crowdsourcing and microfinance. In the African context, crowdfunding is considered as a major asset for financing entrepreneurial activities, yet very few studies are devoted to it. Our study focuses on the operational mechanisms of crowdfunding platforms, the challenges faced by entrepreneurs, and potential solutions for improving this method of financing. To achieve this, we examined seventeen cases of cultural entrepreneurs from Rwanda, Togo, Burkina Faso, Mali, Côte d’Ivoire, Gabon and Cameroun. The analysis reveals that, in the absence of operational platforms in Africa, entrepreneurs turn to those in the West but encounter difficulties in withdrawing funds without having local bank accounts. The lack of knowledge about crowdfunding and the limited internet connectivity further complicates the situation. The practical implications of this research, argue for the creation of crowdfunding platforms in Africa, the training for entrepreneurs, the dissemination of information on CF best practices, the development of digital infrastructure, and the promotion of the use of mobile money to facilitate fundraising. Improving how easy it is to use crowdfunding in Africa could help the continent to develop economically through entrepreneurship and effectively fight poverty as part of the sustainable development goals (SDGs).
Keywords: African Research